Negative Regulation of the Creatine Transporter SLC6A8 by SPAK and OSR1 - Myriam Fezai; Bernat Elvira; Jose Borras; Mossadok Ben-Attia; Zohreh Hoseinzadeh; Florian Lang (Kidney & Blood Pressure Research, 2014)
Background/Aims: Transport regulation involves several kinases including SPAK (SPS1-related proline/alanine-rich kinase) and OSR1 (oxidative stress-responsive kinase 1), which are under control of WNK (with-no-K[Lys]) kinases. The present study explored whether SPAK and/or OSR1 participate in the regulation of the creatine transporter CreaT (SLC6A8), which accomplishes Na+ coupled cellular uptake of creatine in several tissues including kidney, intestine, heart, skeletal muscle and brain. Methods: cRNA encoding SLC6A8 was injected into Xenopus laevis oocytes with or without additional injection of cRNA encoding wild-type SPAK, constitutively active T233ESPAK, WNK insensitive T233ASPAK, catalytically inactive D212ASPAK, wild-type OSR1, constitutively active T185EOSR1, WNK insensitive T185AOSR1 and catalytically inactive D164AOSR1. Transporter activity was determined from creatine (1 mM) induced current utilizing dual electrode voltage clamp. Results: Coexpression of wild-type SPAK and of T233ESPAK, but not of T233ASPAK or of D212ASPAK was followed by a significant decrease of creatine induced current in SLC6A8 expressing oocytes. Coexpression of SPAK significantly decreased maximal transport rate. Coexpression of wild-type OSR1, T185EOSR1 and T185AOSR1 but not of D164AOSR1 significantly negatively regulated SLC6A8 activity. OSR1 again decreased significantly maximal transport rate. Conclusions: Both, SPAK and OSR1, are negative regulators of the creatine transporter SLC6A8.